Α-Synuclein aggregation in neurodegenerative diseases and its inhibition as a potential therapeutic strategy. (26th October 2005) - Paleologou, K.E.; Irvine, G.B.; El-Agnaf, O.M.A.
Abstract : There is strong evidence for the involvement of α-synuclein in the pathologies of several neurodegenerative disorders, including PD (Parkinson's disease). Development of disease appears to be linked to processes that increase the rate at which α-synuclein forms aggregates. These processes include increased protein concentration (via either increased rate of synthesis or decreased rate of degradation), and altered forms of α-synuclein (such as truncations, missense mutations, or chemical modifications by oxidative reactions). Aggregated forms of the protein are toxic to cells and one therapeutic strategy would be to reduce the rate at which aggregation occurs. To this end we have designed several peptides that reduce α-synuclein aggregation. A cell-permeable version of one such peptide was able to inhibit the DNA damage induced by Fe(II) in neuronal cells transfected with α-synuclein (A53T), a familial PD-associated mutation.